2023
DOI: 10.3389/fcvm.2023.1158906
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure versus surgical repair for ruptured sinus of valsalva aneurysm: A systematic review and meta-analysis

Abstract: ObjectivesRuptured sinus of Valsalva aneurysm (RSVA) often has an abrupt onset, and can chest pain, acute heart failure, and even sudden death. The effectiveness of different treatment modalities remains controversial. Thus, we completed a meta-analysis to evaluate the efficiency and safety of traditional surgery vs. percutaneous closure (PC) for RSVA.MethodsWe carried out a meta-analysis using PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), WanFang Data, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…1 A recent meta-analysis of 330 patients from 10 studies showed that percutaneous transcatheter closure was associated with a shorter length of hospital stay but had no statistically significant differences in in-hospital mortality, incidence rates of postinterventional residual shunts, or aortic regurgitation. 6 A surgical approach for SVA repair in our patient who had worsening heart failure symptoms and a high ectopy burden proved to be the best option because it resulted in a good postoperative outcome.…”
Section: Discussionmentioning
confidence: 78%
“…1 A recent meta-analysis of 330 patients from 10 studies showed that percutaneous transcatheter closure was associated with a shorter length of hospital stay but had no statistically significant differences in in-hospital mortality, incidence rates of postinterventional residual shunts, or aortic regurgitation. 6 A surgical approach for SVA repair in our patient who had worsening heart failure symptoms and a high ectopy burden proved to be the best option because it resulted in a good postoperative outcome.…”
Section: Discussionmentioning
confidence: 78%
“…No statistically significant differences were observed in in-hospital mortality, but as expected, percutaneous closure did significantly decrease the average length of hospital stay. Both methods showed similar and low postoperative residual shunts and aortic regurgitation [11]. The second review analyzed the transcatheter method in 407 patients: the success rate of the trancatheter closure was 95.6% with an overall mortality of 0.5%, but 12% of the patients developed complications, the most significant of which were sustained residual shunts in seven, substantial new onset or progression of aortic insufficiency in six and recurrence of SVA in six [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical procedures may result in a high incidence of aortic regurgitation and residual leakage due to invasive injury to the sinus of Valsalva ( 4 ). Therefore, Cullen et al ( 5 ) first conducted transcatheter closure (TCC) of RSVA in 1994, and with the improvement of interventional techniques and the advances in interventional devices, there have been an increasing number of reports on the TCC of RSVA globally ( 6 ). Currently, as far as we know, there is not a specialized occluder for RSVA and the majority of interventional therapies use the Amplatzer ventricular septal defect (VSD) or patent ductus arteriosus (PDA) occluders ( 7-9 ).…”
Section: Introductionmentioning
confidence: 99%